Z-source inverter in five-phase system using simple boost pulse width modulation - Mohd. Shafie, Bakar (2017)
Impedance-source network or known as Z-source network is an X form coupling of the two-port network consists of two inductors and two capacitors. The Z-source network is connected to the input of the H-bridge inverter forming into a Z-source inverter (ZSI). The attributes of ZSI that overcome the conventional inverter, which their accessible of output voltage range in the conventional inverter is restricted to either greater or smaller than the input voltage. This quickly brought interest to the academicians and industry since its inception, a lot of research and development were carried out to improve the existing topology, proposing a new driving scheme, developing control loop and implementing new application. On the other hand, in three-phase inverter operation, the six-step modes of pulse width modulation (PWM) produce the low-frequency torque ripple. Since the lowest frequency torque ripple harmonic in an n-phase machine is caused by the time harmonics of the supply of the order 2n ± 1, an increase in the number of phases of the order 2n ± 1, then the machine is able to resolve the lowfrequency torque ripple. Thus, this thesis is to further enhance the body of knowledge on the driving scheme of multiphase ZSI system since the implementation is rather limited. A system with a higher number of phases would result in lower voltage stress, higher reliability, increase power in the same frame and reduced harmonic distortions. Thus, the research challenge is to fill the gap by using simple boost pulse-width modulation (SBPWM) for the driving scheme of the five-phase ZSI system. SBPWM is a trusted driving scheme since it can be implemented at any ZSI topology, can be embedded in a digital controller, has high robustness and has low mathematics complexity. The research is carried out by remodelling SBPWM to suit the five-phase ZSI system specification under five reference signals that is compared with a carrier signal at switching frequency of 1.5 kHz. The equally contributed at the shoot-through mode in the operation make the system capable of both boosting and bucking operation. It is found that at the 0.253 msec shoot-through time interval gives less than 7% error. The remodelled SBPWM is then implemented on operations below 2 kW via MATLAB@Simulink simulation, where the modulation index (Mi) varied from 0.562 until 1.1 and input DC voltage fixed at 40 V. At Mi 0.62, the five-phase ZSI system offers 4.6% total harmonic distortion (TI-ID) output current for resistive load at the star formation connection. Finally, the result verification is carried out with hardware experiment prototype, where the output current's THD is compiled to the IEEE 519-1992 and EN 61000-3-2 standards.